Has the COVID-19 pandemic led to permanent persistent changes in recreational activity? A case study of a municipal beach - Senetra, Adam; Szczepańska, Agnieszka (Bulletin of Geography. Socio-economic Series, 2022)
Recreational areas in cities deliver numerous social, health and environmental benefits for local communities. They are a desirable element of the urban structure that influences the quality of life. The response to the COVID-19 pandemic, an unprecedented health crisis on a global scale, initially prevented and then significantly limited the use of recreational areas. The pandemic decreased daily activity levels, induced changes in lifestyle and significantly compromised people’s ability to engage in outdoor recreation. In the process of lifting lockdown restrictions, recreational areas play a special role in combatting the consequences of social isolation and restoring access to public spaces. The present study was undertaken to assess the recreational activities of urban dwellers during the COVID-19 crisis. The pandemic’s effect on the leisure behaviour of residents in the Polish city of Olsztyn was evaluated on the example of a sports and recreational centre on Lake Ukiel. The visitor traffic register and the centre’s financial performance were analysed, and a diagnostic survey targeting local residents was conducted online. The results point to a clear decline in the local community’s recreational activities as well as changes in the form and place of recreation.